Impact of P2Y12 inhibitors on cardiovascular outcomes of Korean acute myocardial infarction patients with baseline thrombocytopenia - Oh, Seok; Jeong, Myung Ho; Cho, Kyung Hoon; Kim, Min Chul; Sim, Doo Sun; Hong, Young Joon; Kim, Ju Han; Ahn, Youngkeun (Frontiers in Cardiovascular Medicine, 2022)
Background: Antiplatelet therapy is crucial for managing acute myocardial infarction (AMI) and reducing adverse ischemic events after percutaneous coronary intervention (PCI) with drug-eluting stents. However, the ideal P2Y12 inhibitor for patients—particularly East Asians—with AMI and low platelet levels remains unknown. We evaluated the impact of various potencies of P2Y12 receptors on major cardiovascular outcomes of AMI patients with thrombocytopenia in Korea. Methods: We analyzed the clinical and outcome data of 800 AMI patients with baseline platelet counts <150 × 103/μL who underwent PCI between November 2011 and June 2015. All patient data were obtained from the Korea Acute Myocardial Infarction Registry‒National Institutes of Health registry. Subjects were allocated to group A (n=244; treated with potent P2Y12 inhibitors) or group B (n=556; treated with clopidogrel). The primary endpoint was major adverse cardiac and cerebrovascular events (MACCEs). Results: At the 3-year follow-up, clinical outcomes appeared better in group A than in Group B. However, after propensity score weighting-adjusted analysis, these findings were statistically attenuated, showing a similar incidence of MACCEs between the two groups. Conclusions: Clopidogrel may be reasonable for patients with low platelet counts and is associated with comparable outcomes to potent P2Y12 inhibitors for Korean AMI patients.